Embedding Federalism in the South Sudan’s Permanent Constitution: Achieving Unity in Diversity Policy - Santino Ayuel Longar Dau (Journal of Contemporary Governance and Public Policy, 2022)
As South Sudan emerges from a brutal conflict, the 2018 Agreement mandates the Government to initiate and adopt a federal system of government through a new constitutional dispensation during the Transitional Period (2020-2024). The central issue in this paper revolves around the nature of the federal system that South Sudan should adopt to govern itself. The paper finds that while the federalism debate has historical pedigree in the political thought among the people of the Republic of South Sudan, the type of federal system to be adopted lies in the discretion of the framers. In light of this and having regard to global practice and experience of federal systems, the federal system in South Sudan should be guided by several factors such as management of ethnic conflicts, cultural compatibility, economic viability of constituent units, territoriality, and population sizes.